Observation unit use among patients with cancer following emergency department visits: Results of a multicenter prospective cohort from CONCERN. (4th December 2021) - Klotz, Adam D.; Caterino, Jeffrey M.; Durham, Danielle; Felipe Rico, Juan; Pallin, Daniel J.; Grudzen, Corita R.; McNaughton, Caroline; Marcelin, Isabelle; Abar, Beau; Adler, David; Bastani, Aveh; Bernstein, Steven L.; et al.
Abstract: Purpose: Emergency department (ED) visits by patients with cancer frequently end in hospitalization. As concerns about ED and hospital crowding increase, observation unit care may be an important strategy to deliver safe and efficient treatment for eligible patients. In this investigation, we compared the prevalence and clinical characteristics of cancer patients who received observation unit care with those who were admitted to the hospital from the ED. Methods: We performed a multicenter prospective cohort study of patients with cancer presenting to an ED affiliated with one of 18 hospitals of the Comprehensive Oncologic Emergency Research Network (CONCERN) between March 1, 2016 and January 30, 2017. We compared patient characteristics with the prevalence of observation unit care usage, hospital admission, and length of stay. Results: Of 1051 enrolled patients, 596 (56.7%) were admitted as inpatients, and 72 (6.9%) were placed in an observation unit. For patients admitted as inpatients, 23.7% had a length of stay ≤2 days. The conversion rate from observation to inpatient was 17.1% (95% CI 14.6–19.4) among those receiving care in an observation unit. The average observation unit length of stay was 14.7 h. Patient factors associated ED disposition to observation unit care were female gender and low Charlson Comorbidity Index. Conclusion: In this multicenter prospective cohort study, the discrepancy between observation unit care use and short inpatient hospitalization may represent underutilization of this resource and a target for process change.